2021
DOI: 10.3389/fcell.2021.688352
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-Dependent Regulation of Small GTPases in Membrane Trafficking: From Cell Biology to Human Diseases

Abstract: Membrane trafficking is critical for cellular homeostasis, which is mainly carried out by small GTPases, a class of proteins functioning in vesicle budding, transport, tethering and fusion processes. The accurate and organized membrane trafficking relies on the proper regulation of small GTPases, which involves the conversion between GTP- and GDP-bound small GTPases mediated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). Emerging evidence indicates that post-translational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 166 publications
(202 reference statements)
1
1
1
Order By: Relevance
“…Despite the overall trend of increased ubiquitylation with aging, a fraction of sites showed decreased ubiquitylation (Figure 1E). When assessing which cellular component categories were affected by these changes, GO enrichment analysis revealed that the myelin sheath, mitochondrion, and GTPase complex showed an increase in ubiquitylation, the latter in agreement with a previous report (Lei et al, 2021) (Figure 1E). In contrast, proteins belonging to the synaptic compartment were enriched among those showing decreased ubiquitylation with aging (Figure 1E).…”
Section: Aging Affects Ptms In the Brainsupporting
confidence: 91%
“…Despite the overall trend of increased ubiquitylation with aging, a fraction of sites showed decreased ubiquitylation (Figure 1E). When assessing which cellular component categories were affected by these changes, GO enrichment analysis revealed that the myelin sheath, mitochondrion, and GTPase complex showed an increase in ubiquitylation, the latter in agreement with a previous report (Lei et al, 2021) (Figure 1E). In contrast, proteins belonging to the synaptic compartment were enriched among those showing decreased ubiquitylation with aging (Figure 1E).…”
Section: Aging Affects Ptms In the Brainsupporting
confidence: 91%
“…In general, a ubiquitination-dependent regulation is important for balancing MyD88-dependent and –independent pathways which signal through TRIF (conditionally TRIF3 or TRIF6), TRAMs and TAK. 30 While it is not common for TLR2 to signal in a MyD88-independent pathway, within the scope of this study, we found little evidence to show that TLR2 compensation for ARF6 loss was being mediated by MyD88. Only one study has identified that during infection by Porphyromonas gingivalis , a gram negative bacteria, TLR2 can upregulate TNFα and cytokines in a MyD88-independent manner.…”
Section: Discussioncontrasting
confidence: 61%
“…Additionally, ARF6 function is regulated through ubiquitination which further impacts cellular migration and invasion. 29,30 Importantly on day 7, we observed an enrichment of cell cycle related terms surround the regulation of mitosis and chromosomal segregation (Figure 2 A), which we did not observe upon shASAP1 treatment (Supplementary Figure S2 B). These terms align with our findings that PDAC cells subject to ARF6-depletion, but not ASAP1-depletion, produce an adaptive proliferation response starting at day 7 (Figure 1 C).…”
Section: Gene Ontology Enrichment Analysis Of Time-resolved Transcrip...mentioning
confidence: 76%